Determinantes da produtividade do trabalho na economia brasileira durante o período 2000-2020 - Luiz Dias Bahia (Instituto de Pesquisa Econômica Aplicada (IPEA), 2025)
– This paper computes the labor productivity of the Brazilian economy from 2000 to 2020 utilizing the input-output matrix methodology. The results are achieved using as key causes variables selected from the cited matrix. We conclude that technological change, consumption and exports are the main causes of labor productivity development in Brazil from 2000 to 2020. Investment is another key cause that could be more important if it had been stronger.
Keywords: D24; E24; 330; labour productivity; causes; input-output matrix